2022
DOI: 10.3899/jrheum.220139
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Anti-Ro52 Antibodies in Anti-MDA5 Antibody–Positive Dermatomyositis Is Highly Associated With Rapidly Progressive Interstitial Lung Disease and Mortality Risk

Abstract: Objective Interstitial lung disease (ILD) is a common extramuscular complication contributing to significant morbidity and mortality in anti-melanoma differentiation associated gene 5 positive dermatomyositis (anti-MDA5+ DM). We conducted this study to investigate the association of anti-Ro52 antibodies with clinical characteristics and prognosis in anti-MDA5+ DM patients. Methods We assessed a cohort of 246 patients with anti-MDA5+ DM. To calculate hazard ratios (HRs) and 95% confidence intervals (95% CIs) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
3
22
1
Order By: Relevance
“…Statistically significant younger age at disease onset in Ro52/SSA + patients was noted in our cohort at 44.8 years at age at onset versus 51.2 years in Ro52/SSA − patients. This association of Ro52/SSA positivity with earlier age at onset is in contrast to the literature, which did not demonstrate any association with age 5,6,9 . In addition, the age at onset for Ro52/SSA + patients was younger than the patients in the literature reviewed.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Statistically significant younger age at disease onset in Ro52/SSA + patients was noted in our cohort at 44.8 years at age at onset versus 51.2 years in Ro52/SSA − patients. This association of Ro52/SSA positivity with earlier age at onset is in contrast to the literature, which did not demonstrate any association with age 5,6,9 . In addition, the age at onset for Ro52/SSA + patients was younger than the patients in the literature reviewed.…”
Section: Discussioncontrasting
confidence: 94%
“…In addition, the age at onset for Ro52/SSA + patients was younger than the patients in the literature reviewed. Despite small numbers, patients of Asian ethnicity were more frequently identified as Ro52/SSA + , similar to the multiple studies originating from China 4,6,7,9 . No other statistically significant demographic associations were identified between groups to include female sex, which was identified by Bozzalla-Cassione et al 18 …”
Section: Discussionsupporting
confidence: 67%
“…Anti-Ro52 antibodies still represent one of the most common autoantibodies in patients with connective tissue diseases ( 51 , 52 ), with high prevalence of ILD with unfavorable outcomes ( 47 49 ). In particular cases, the coexistence of anti-Ro52 and anti-MDA5 antibodies has been associated with aggressive and rapidly progressive ILD in anti-MDA5 syndrome ( 53 , 54 ) but there are conflicting data on the prognostic role of anti-Ro52 antibodies when associated with other MSA ( 55 , 56 ). Of note, signs of lung fibrosis at HRCT were described in patients with ILD in mixed connective tissue disease and anti-Ro52 positivity ( 57 ), while lower prevalence of fibrosing ILD was found in a cohort of anti-Ro52 positive subjects with Sjogren’s syndrome compared to Ro52-negative patients ( 58 ).…”
Section: Autoantibodies In Idiopathic Inflammatory Myopathy-ild At Ri...mentioning
confidence: 99%
“…A summary of relevant studies, including the current report from Lv et al, is given in the Table. 3,4,[7][8][9][10][11][12][13][14][15] All but 1 study 3 found that the presence of anti-Ro52 with anti-Jo1 was associated with more severe ILD and poorer outcomes. Notably similar findings were reported in a large cohort of children with juvenile myositis in the United States, where ILD is far less common.…”
mentioning
confidence: 95%
“…In a study published in this issue of The Journal of Rheumatology, Lv et al report retrospectively on a large regional cohort of 246 patients with myositis-associated ILD and positive for anti-MDA5 gathered from 10 centers. 4 Anti-Ro52 was present in 158 of the 246 anti-MDA5 patients (64%) and was significantly associated with a higher rate of development of RP-ILD and about twice the mortality rate (29% compared to 16% in anti-Ro52negative patients). There are major limitations in such a retrospective study, including selection bias, treatment effects, and the lack of adjustment for person-years at risk.…”
mentioning
confidence: 96%